Can healthcare adapt to a world of tightening ecological constraints? Challenges on the road to a post-growth future. (17th November 2020) - Hensher, Martin; Zywert, Katharine
Abstract : Martin Hensher and Katharine Zywert examine some of the difficult changes that healthcare systems will need to make in the Anthropocene epoch